Three new species of Tenuipalpus Donnadieu (Acari, Tenuipalpidae) from the State of São Paulo, Brazil - Feres, Reinaldo J.f.; Hernandes, Fábio A. (Zootaxa, 2006)
Three new species of Tenuipalpus, T. carlosflechtmanni n. sp., T. moraesi n. sp. and T. ariauae n. sp., collected on wild plants in Brazil, are described and illustrated.